From Expression to Connection: Decoding Sana All’s Linguistic Meanings in Communication Context - Dangalao, Tong Kabenbelan (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
very age group and generation uses different lingo, jargon, and forms of communication in casual conversations. These lingos could be introduced by the fashions, significant events, radio shows, movies, TV shows, songs, and literature of their time, among many other devices. Additionally, technology has changed some words, adding new ones that are more inventive and simpler to type. The study aimed to analyze the linguistic meaning of "Sana All" used by the Grade 11 Senior High School students in Cotabato City National High School – Annex (Buaya-Buaya Site). Colaizzi’s phenomenological method of inquiry was employed in this study. The researcher utilized the Focal Group Discussion (FGD) in gathering data. The study's findings revealed that the phrase "Sana All" is used by student participants in Social Media, School, Home, and the Real World. The phrase connotes admiration, appreciation, wishing for something to happen, and strengthening relationships with others. Various meanings were generated depending on the communication setting. The researcher concluded that students use the phrase "Sana All" in various communication settings. They use this phrase when wishing, admiring, appreciating, and strengthening relationships with others. Finally, the researcher produced a linguistic concept on the teaching strategies on pragmatics and semantics where the teacher can adopt the trendy phrase to be included when teaching the linguistic concept of pragmatics and semantics.